Risk Factors and Prevention of Stomach Cancer, Excluding Helicobacter pylori - Seung-Woo Lee (Yong Chan Lee, 2024)
Gastric cancer is a significant health problem owing to its high incidence and mortality rate. The risk factors for gastric cancer include both uncontrollable (e.g., age, sex, and genetic predisposition) and controllable factors (e.g., Helicobacter pylori infection, smoking, alcohol consumption, obesity, and high-salt diets). Although treatment of H. pylori infections has been implemented as a primary preventive measure, the risk of gastric cancer may persist, highlighting the need for additional preventive measures. This review discusses various risks and protective factors associated with gastric cancer, studies conducted on these factors, and chemoprevention. Smoking is a risk factor for this disease; thus, is not recommended and current smokers are encouraged to quit because cessation can reduce the risk of gastric cancer. Excessive alcohol intake has been reported to increase the risk of gastric cancer as has the consumption of high-salt foods that can damage the gastric mucosa. Additionally, increasing the intake of fruits and vegetables, known for their protective effects against gastric cancer, can aid in its prevention. Studies on chemopreventive agents, including nonsteroidal anti-inflammatory drugs (e.g., aspirin), statins, and metformin, have been reported; however, evidence of their effectiveness remains insufficient to recommend these agents as preventive treatments. Additional well-planned studies on preventive medications and dietary approaches are necessary.